Possibility of local pair existence in optimally doped SmFeAsO1-х in pseudogap regime - Solovjov, A.L.; Svetlov, V.N.; Stepanov, V.B.; Sidorov, S.L.; Tarenkov, V.Yu.; D’yachenko, A.I.; Agafonov, A.B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
We report the analysis of pseudogap Δ* derived from resistivity experiments in FeAs-based superconductor SmFeAsO0.85, having a critical temperature Tc = 55 K. Rather specific dependence Δ*(T) with two representative temperatures followed by a minimum at about 120 K was observed. Below Ts ≈ 147 K, corresponding to the structural transition in SmFeAsO, Δ*(T) decreases linearly down to the temperature TAFM ≈ 133 K. This last peculiarity can likely be attributed to the antiferromagnetic (AFM) ordering of Fe spins. It is believed that the found behavior can be explained in terms of Machida, Nokura, and Matsubara theory developed for the AFM superconductors.